Sinhazinha Brasilina versus Dona Manuela : o discurso de Monteiro Lobato sobre a língua do Brasil - Carvalho, Sheila Cristiane de (2013)
This study aimed at analyzing Monteiro Lobato’s enunciations about the Brazilian language based on the French discourse analysis, having as background the controversy between separatists and legitimists. Among the writings that compose Lobato’s large work, the comments about the linguistic theme that plagued the Brazilian intelligentsia in the early twentieth century are abundant, thus justifying systematic investigation of his thought. One sought to come near the feelings attributed by the writer to the linguistic differentiation ongoing in Brazil, the dialogue with the modernist movement, the controversy with the conservatives. One also sought to understand the ethos of the enunciator in his battle to mean the alterity of the Brazilian Language in relation to the European Portuguese and to form a national identity. The approach proposed by Dominique Mainguenean (2008) was used as central support for the reading of the enunciations, in particular the first and the second hypothesis that state respectively, the primacy of the inter-discourse over the discourse and the controversy as inter-incomprehension. The concept of discursive ethos, such as that discussed by Maingueneau (1997; 2004; 2008; 2011), Ruth Amossy (2011) and Salgado and Motta (2008) also integrated the device of analysis to be mobilized in the reading of the corpus. As it is an archive research, the corpus was formed with discursive sequences (SDs) extracted from Monteiro Lobato’s work, based on the principle of the thematic trajectory. The analysis of the corpus showed that the place of which Lobato speaks is that of the separatist’s, however, this place, far from being a territory totally conquered, is a territory under litigation, disputed with the legitimist that advocates the maintenance of the Portuguese linguistic domain, even when the other colonial ties were broken. Advocating the linguistic emancipation of Brazil, Monteiro Lobato was mocking, ironic, aggressive, irreverent, obstinate, stubborn, and, seldom thoughtful. He spoke in a tone of a genuine separatist that declares a critical nationalist fighting with the legitimists/conservatives that defended the maintenance of the chains that still linked Brazil to Portugal.